2010
DOI: 10.1590/s0100-83582010000100018
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia de herbicidas inibidores da ACCase no controle de gramíneas em lavouras de soja

Abstract: Objetivou-se com este trabalho avaliar a eficácia de herbicidas inibidores da ACCase, aplicados isoladamente ou em associações, no controle das espécies de plantas daninhas pertencentes à família das gramíneas Brachiaria decumbens, Digitaria ciliaris, Eleusine indica, Brachiaria plantaginea e Cenchrus echinatus, na cultura da soja. O experimento foi conduzido em campo, em delineamento de blocos ao acaso com quatro repetições. Os tratamentos avaliados foram: clethodim (84 g ha-1), clethodim + quizalofop-p-ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
2
11
0
8
Order By: Relevance
“…Confirming the findings, Barroso et al (2010) found that in application of ACCase inhibiting herbicides in E. indica plants, sethoxydim provided the worst performances of control. On the other hand, haloxyfop-methyl herbicide resulted in a control above 90%.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Confirming the findings, Barroso et al (2010) found that in application of ACCase inhibiting herbicides in E. indica plants, sethoxydim provided the worst performances of control. On the other hand, haloxyfop-methyl herbicide resulted in a control above 90%.…”
Section: Resultssupporting
confidence: 66%
“…According to Barroso et al (2010), in a study of Urochloa decumbens, Digitaria ciliaris, Eleusine indica, Urochloa plantaginea and Cenchrus echinatus grasses, applying ACCase inhibiting herbicides, haloxyfop-methyl showed greater action spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Tal resultado pode ser explicado pelo fato destes herbicidas serem empregados para o controle de plantas daninhas monocotiledôneas, sendo utilizados, portanto, de forma seletiva em culturas dicotiledôneas (Jasper et al, 2015). Segundo Barroso et al (2010), o mecanismo que inibe a ACCase, bloqueia a síntese de lipídeos apenas nas plantas susceptíveis, impossibilitando a formação da membrana celular e causando desestruturação dos tecidos em formação.…”
Section: Seletividade De Herbicidas Aplicados Em Pós-emergência Na Cuunclassified
“…In addition, weed species respond differently to herbicides when isolated or in combination (BARROSO et al, 2010) and in different weed plant stages. The more advanced the stage is, higher will be the herbicide dose required for an efficient control (DORS et al, 2010).…”
Section: Introductionmentioning
confidence: 99%